Registering Muslim Marriages: Penghulu, Modin, and the Struggles for Influence - Muhammad Latif Fauzi (Al-Jami'ah: Journal of Islamic Studies, 2019)
This article deals with the position of penghulu and modin and examines how they struggle for influence in the context of marriage registration. Materials of this article result from my ethnography in a village in East Java in 2017. I did interviews, participant observation and document analysis and applied the “state-in-society” approach to analyse the finding. In this article, I suggest that to maintain their influence, penghulu tend not to present themselves as ulama although their identity as a religious authority is highly important. Instead, penghulu identify themselves as the state agency by materialising their authority to provide state recognition of Muslim marriages into the resource of power. On the other hand, modin play important roles in bridging the relationship between the state and society. Modin find themselves subject to compromise between competing legal orders so that they sometimes need to produce an alternative legal norm to make their intermediary role possible. [Artikel ini mendiskusikan posisi penghulu dan modin serta melihat bagaimana mereka berjuang untuk berebut pengaruh di masyarakat dalam hal pencatatan perkawinan. Bahan-bahan artikel ini diperoleh dari etnografi yang saya lakukan di sebuah desa di Jawa Timur pada tahun 2017. Saya melakukan wawancara, observasi partisipatif, dan analisis dokumen serta menggunakan pendekatan “state-in-society” untuk menganalisa temuan lapangan. Saya menyimpulkan bahwa untuk mempertahankan pengaruhnya, penghulu cenderung tidak menampilkan dirinya sebagai ulama meskipun identitas mereka sebagai otoritas agama tetap penting. Sebaliknya, mereka mengidentifikasi diri mereka sebagai agen negara dengan mentransformasi otoritas untuk memberikan pengakuan negara atas perkawinan sebagai sumber kekuasaan. Selain itu, modin memiliki peran penting dalam menjembatani hubungan negara dan masyarakat. Modin berada dalam situasi kompetisi antar norma hukum sehingga terkadang perlu untuk membuat norma hukum alternatif untuk mempertahankan posisi mereka.